2011
DOI: 10.1371/journal.pone.0024491
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of a Novel Human Adenovirus with a Serologically Unique Hexon and a Recombinant Fiber Gene

Abstract: In February of 1996 a human adenovirus (formerly known as Ad-Cor-96-487) was isolated from the stool of an AIDS patient who presented with severe chronic diarrhea. To characterize this apparently novel pathogen of potential public health significance, the complete genome of this adenovirus was sequenced to elucidate its origin. Bioinformatic and phylogenetic analyses of this genome demonstrate that this virus, heretofore referred to as HAdV-D58, contains a novel hexon gene as well as a recombinant fiber gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 23 publications
1
51
0
3
Order By: Relevance
“…Currently, the typing can be done through PCR amplification and sequencing of the hexon, penton, and fiber genes. The hexon gene sequence analysis has widely been used for the classification of adenovirus types; however, sequence analysis of the fiber gene has also been incorporated to determine the recombination events in the adenovirus genotype (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the typing can be done through PCR amplification and sequencing of the hexon, penton, and fiber genes. The hexon gene sequence analysis has widely been used for the classification of adenovirus types; however, sequence analysis of the fiber gene has also been incorporated to determine the recombination events in the adenovirus genotype (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Análisis de recombinación para la especie D En un intento de aclarar la inconsistencia genotípica observada anteriormente con la muestra Py52A, se aisló el virus a partir de cultivo celular, y fueron diseñados nuevos cebadores para amplificar una región de 1572-nt del gen hexon incluyendo parte del bucle 1, que contiene 6 regiones hiper variables (HVR1-6), y el bucle 2, que contiene la HVR-7, donde comúnmente son reportados eventos de (23) recombinación intra-génica . Este fragmento de 1572-nt fue empalmado a la región C4 anteriormente obtenida, resultando en un fragmento final de 2370-nt (renombrado Py52A-HexCult).…”
Section: Análisis De Recombinaciónunclassified
“…So far, greater than 60 types of HAdV have been identified and grouped into seven species, named HAdV-A through HAdV-G (Jones et al, 2007;Ishiko et al, 2008;Walsh et al, 2009Walsh et al, , 2010Walsh et al, , 2011Robinson et al, 2011a;Kaneko et al, 2011b;Liu et al, 2011). HAdVs cause a range of illnesses, including pharyngoconjunctival fever (PCF), which is characterized by fever, pharyngitis and conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the hexon gene, genetic analyses revealed that the penton base gene, fibre gene and the early region 3 (E3) are also type-specific (Kaneko et al, 2009;Robinson et al, 2011b). Sequence analysis of these genes has led to the recent identification of novel types of recombinant HAdV-D (Walsh et al, 2009;Robinson et al, 2011a;Kaneko et al, 2011bKaneko et al, , 2011cLiu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%